Воины в росписях ранневизантийских склепов некрополя Боспора - Зинько, Е.А. (Материалы по археологии, истории и этнографии Таврии, 2008)
Погребальные памятники некрополя Пантикапея-Боспора конца III -V вв. н.э. определенным образом отображают изменения, происходившие в социальной и культурной жизни Боспорского царства, когда военизация быта определялась необходимостью защищать рубежи государства от участившихся набегов со стороны кочевых племен. Burial monuments of the necropolis of Panticapeum-Bosporus dating back to the Зrd - 5th century represent changes in social and cultural life of Bosporus Kingdom when militarization of the way of life was determined by the necessity to defend the borders of the country from forays of nomadic tribes that became more and more frequent. In Panticapeum crypts of that time among burial equipment armaments was met rather frequentiy - swords, daggers, spear and arrow heads, remnants of shields. Horse harness, bridle, and, occasionally, a horse were put together with the deceased. Rich citizens of Bosporus decorated the walls of these crypts with paintings in «geometric style» combined with religious symbolic images with pictures that, obviously, represented real life of the buried, and in many cases they were connected with military affairs.